Upaya Peningkatan Pemahaman Konsep Melukis Sudut Istimewa dengan Metode Pembelajaran Matematika Realistik di Kelas 7E SMP Negeri 9 Kota Blitar - Yuliati (Civiliza Publishing, 2021)
Abstract. Mathematics education in elementary school is the beginning of a child's beginning to explore his ability to understand concepts in mathematics and the knowledge gained will greatly influence him at the next level of education. In learning to paint special angles in Class 7C of SMP Negeri 9 Blitar City, for the 2020/2021 academic year, it can be seen that there are still many students who do not understand the concept. This is due to the frequent online learning during the corona pandemic, so teachers have not yet completed learning. Such conditions require teachers to conduct research. The research used is a qualitative research on learning Mathematics with the type of Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The method used to solve problems in learning to measure angles is the Realistic Mathematics method, which is a learning method that links children's real life experiences with mathematical ideas into classroom learning, it is important to do so that learning is meaningful.